Intensi Berwirausaha Mahasiswa : Peran Kreativitas dan Theory of Planned Behavior - Kurnia Oktaviani, Leny; Noviani, Leny (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
The purpose of this research are to determine the influence of creativity, entrepreneurial attitude, perceived behavioral control, and subjective norms on the entrepreneurial intention of students at Sebelas Maret University, Surakarta This research is quantitative research with descriptive analysis. The sample in this study consisted of 381 active students at Sebelas Maret University, Surakarta who were currently taking or had previously taken entrepreneurship courses. Data collection was conducted using a questionnaire distributed via Google Forms. Data analysis used Structural Equation Modeling (SEM). The results of this study indicate that creativity, entrepreneurial attitude, perceived behavioral control, and subjective norms have a positive and significant effect on entrepreneurial intentions of active students of Sebelas Maret University, Surakarta. The conclusion of this study proves that the Theory of Planned Behavior has a relationship with the level of entrepreneurial intentions of students. The transformation of the Indonesian economy can be attempted by increasing the number of entrepreneurs through improving the quality of entrepreneurship education in universities.